CYP1A1 Ile462Val Polymorphism Is Associated with Cervical Cancer Risk in Caucasians Not Asians: A Meta-Analysis - Wang, Li-Na; Wang, Fen; Liu, Jie; Jin, Ying-Hui; Fang, Cheng; Ren, Xue-Qun (Frontiers in Physiology, 2017)
Objective: Previous studies have reported that Ile462Val polymorphism in the gene Cytochrome P450 1A1 (CYP1A1) is associated with the risk of cervical cancer, but inconsistent results have emerged. Hence, we performed this updated and cumulative meta-analysis to ascertain a more accurate association between CYP1A1 Ile462Val polymorphism and risk of cervical cancer. Methods: Studies involving the CYP1A1 Ile462Val polymorphism associated with cervical cancer risk were searched from the databases of PubMed, Scopus, ScienceDirect, and Chinese National Knowledge Infrastructure (CNKI). The strength of correlation was evaluated through calculating summary odds ratios (ORs) with the corresponding 95% confidence intervals (95% CIs). Subgroup analyses according to ethnicity, source of control and HWE were completed to further explore specific association between the polymorphism and the cancer risk. Results: Altogether, 11 eligible case-control studies were ultimately encompassed into the current meta-analysis, with 1,932 patients and 2,039 healthy controls. The total analysis revealed a borderline relationship between CYP1A1 Ile462Val polymorphism and cervical cancer risk in general population. Interestingly, after subgroup analyses based on ethnicity and source of control, the polymorphism increased the susceptibility of cervical cancer in Caucasian (G vs. A: OR=1.97, 95% CI=1.24-3.13; GG vs. AA: OR=3.24, 95% CI=1.24-8.46; GA vs. AA: OR=1.62, 95% CI=1.25-2.10; GA+GG vs. AA: OR=1.68, 95% CI=1.16-2.43; GG vs. AA+GA: OR= 2.73, 95% CI=1.05-7.10) and population-based (G vs. A: OR=1.49, 95% CI= 1.10-2.02; GA vs. AA: OR=1.41, 95% CI=1.20-1.67; GA+GG vs. AA: OR=1.40, 95% CI=1.19-1.64) groups. Conclusion: The CYP1A1 Ile462Val polymorphism may enhance the susceptibility to cervical cancer in Caucasian females.